Assortative Mating Is a Natural Consequence of Heritable Variation in Preferences and Preferred Traits - Harper, Kaitlyn T.; Zietsch, Brendan P. (Psychological Science, 2025)
Assortative mating—the tendency to choose partners similar to oneself—is a ubiquitous phenomenon in mate choice. Despite numerous proposed explanations, a parsimonious mechanism has been overlooked: When individuals choose mates on the basis of heritable traits and preferences, offspring inherit a trait and the corresponding preference from each parent, creating genetic correlations that link having a trait to preferring that same trait. We evaluated this mechanism with an agent-based model simulating 100 generations in which agents, with traits and preferences each uniquely determined by 40 loci, chose reproductive partners based on preferences. Genetic correlations formed between preferences and preferred traits, as well as between partner traits (i.e., assortative mating), demonstrating that heritable variation in preferences and preferred traits is sufficient to drive assortative mating. We presented a toy model here, so we cannot speak to the robustness of such genetic correlations or to the relative explanatory power of this mechanism over others.